2013
DOI: 10.1111/ajco.12112
|View full text |Cite
|
Sign up to set email alerts
|

Registry of gastric cancer treatment evaluation (REGATE): I baseline disease characteristics

Abstract: These results provide a comprehensive database representative of gastric cancer disease characteristics and treatment patterns across the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 6 publications
3
33
2
Order By: Relevance
“…While the majority of first-line regimens administered to patients in this study consisted of a platinum agent and fluoropyrimidine as per eligibility criteria, second-line therapies varied widely, and include regimens that consisted of various single-agent fluoropyrimidines, doublet and triplet regimens, and single-agent taxanes. In a large, international prospective study of gastric cancer treatment (REGATE I), the use of a taxane such as paclitaxel, docetaxel, or irinotecan was reportedly the suggested second-line treatment for gastric cancer in Asia, though fewer than 10% of patients in the present sample were prescribed a taxane [1]. Other recent studies have reported a survival advantage associated with treatment with a second-line taxane such as docetaxel, or with irinotecan for cancers refractory to fluoropyrimidine and platinum treatment when compared to BSC [13,14].…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…While the majority of first-line regimens administered to patients in this study consisted of a platinum agent and fluoropyrimidine as per eligibility criteria, second-line therapies varied widely, and include regimens that consisted of various single-agent fluoropyrimidines, doublet and triplet regimens, and single-agent taxanes. In a large, international prospective study of gastric cancer treatment (REGATE I), the use of a taxane such as paclitaxel, docetaxel, or irinotecan was reportedly the suggested second-line treatment for gastric cancer in Asia, though fewer than 10% of patients in the present sample were prescribed a taxane [1]. Other recent studies have reported a survival advantage associated with treatment with a second-line taxane such as docetaxel, or with irinotecan for cancers refractory to fluoropyrimidine and platinum treatment when compared to BSC [13,14].…”
Section: Discussionmentioning
confidence: 87%
“…Gastric cancer is the fourth most common cancer worldwide and the second most common cause of cancer-related deaths [1,2]. The incidence of gastric cancer is highest in East Asian countries and in some parts of South America, while its occurrence is lower in North America and Africa [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations